Respuesta :

we are given

[tex]y=cos^{-1}(x-\pi)[/tex]

Since, we have to find inverse function

step-1:

Set y=f(x)

It is already there

step-2:

Switch x and y

[tex]x=cos^{-1}(y-\pi)[/tex]

step-3: Solve for y

We can take cos on both sides

[tex]cos(x)=cos(cos^{-1}(y-\pi))[/tex]

we can simplify it

[tex]cos(x)=y-\pi[/tex]

now, we can solve for y

[tex]cos(x)+\pi=y-\pi+\pi[/tex]

[tex]cos(x)+\pi=y[/tex]

[tex]y=\pi +cos(x)[/tex]..............Answer


Answer:

The answer is C

Step-by-step explanation: